Raindrop Energy Impact on the Distribution Characteristics of Splash Aggregates of Cultivated Dark Loessial Cores - Fu, Yu; Li, Guanglu; Wang, Dong; Zheng, Tenghui; Yang, Mingxi (Water (Basel), 2019)
To determine the effect of different rainfall energy levels on the breakdown of soil aggregates, this study analyzed the soil splash erosion amounts and the distribution of particle sizes under six rainfall conditions (rainfall energy: 2.41 × 10−5–22.4 × 10−5 J m−2 s−1 and 1.29 × 10−4 J m−2 s−1) at five splash distances (from 0–10 cm to 40–50 cm). Cores of the size 10 × 20 cm of undisturbed cultivated dark loessial soil were selected in tree replicates as the research subject. The results indicated that splashed aggregates were distributed mainly at splash distances of 0–20 cm, which accounted for 66%–90% of the total splash erosion amount. The splash erosion amount significantly decreased exponentially with increasing splash distance for the same rainfall energy (p < 0.01). The splash erosion amount significantly increased in the power function relationship with increasing rainfall energy at the same splash distance (p < 0.05). A model was obtained to predict the splash erosion amount for rainfall energy and splash distance. The fractal dimension (D) of the aggregates showed a downward opening parabolic relationship with raindrop energy. The maximal value of the rainfall energy was 1.286 × 10−4 J m−2 s−1, which broke the aggregates to the largest degree. Enrichment ratio (ER) values for fragments >2 mm were close to 0. A particle size of 0.25 mm was the critical particle level for splash erosion.